Como o processo artístico em dança pode ser abordado e analisado, possibilitando uma maior interação entre figurino, movimento e ato criativo, a fim de alcançar uma prática mais simbiótica? - LAGO, Deborah Marques (2018)
This specific work was developed as a Work for Conclusion of the Course (BA) Hons Dance held by Edge Hill University (UK). It intends to analyse and to discuss the creative process – as in movement combined to the use of the costume – of British and Brazilian creative dancers and performers, using a qualitative quantitative questionnaire (similar to the half-structured interviews of the Brazilian methodological model). This research tries to reveal the importance of including costume in Contemporary Dance creative process without creating any hierarchy, in a way of demonstrating its relevance for the dancer‟s creative act as well as the other elements, considered more important for the choreographic construction as a whole. The figure of the creative dancer turned up to be essential to the essay that approaches the analysis to the researcher‟s own practice, including the discussion about the role of the costume in many creative processes from the performer‟s point of view and experience. The plurality permitted by contemporary dance incurs in involving the concepts of intention, creative act and form as intermediaries of the process of creating movement and costume, so that is possible to achieve a more symbiotic practice.